MiR-125b Reduces Porcine Reproductive and Respiratory Syndrome Virus Replication by Negatively Regulating the NF-κB Pathway - Wang, Dang; Cao, Lu; Xu, Zheng; Fang, Liurong; Zhong, Yao; Chen, Quangang; Luo, Rui; Chen, Huanchun; Li, Kui; Xiao, Shaobo (PloS one, 2013)
Porcine reproductive and respiratory syndrome virus (PRRSV) is an Arterivirus that has been devastating the swine industry worldwide since the late 1980s. To investigate the impact of cellular microRNAs (miRNAs) on the replication of PRRSV, we screened 10 highly conserved miRNAs implicated in innate immunity or antiviral function and identified miR-125b as an inhibitor of PRRSV replication. Virus titer and western blot assays demonstrated that miR-125b reduced PRRSV replication and viral gene expression in a dose-dependent manner in both MARC-145 cell line and primary porcine alveolar macrophages. Mechanistically, miR-125b did not target the PRRSV genome. Rather, it inhibited activation of NF-κB, which we found to be required for PRRSV replication. PRRSV, in turn, down-regulated miR-125b expression post-infection to promote viral replication. Collectively, miR-125b is an antiviral host factor against PRRSV, but it is subject to manipulation by PRRSV. Our study reveals an example of manipulation of a cellular miRNA by an arterivirus to re-orchestrate host gene expression for viral propagation and sheds new light on targeting host factors to develop effective control measures for PRRS.